2019
DOI: 10.1007/s00202-019-00824-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of single-phase self-excited induction generators of various rotor cages

Abstract: The paper deals with a simulation study of influence of conductive material of the rotor squirrel cage on output characteristics of single-phase self-excited induction generators. For calculation of performance characteristics, two-dimensional field-circuit model of the single-phase induction generator was applied. A comparison of self-excitation waveforms of terminal voltage and load characteristics of the generators for rotor bars of the same shape, made of aluminium and copper, was presented. The obtained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The induced emf and current in the stator winding will continue to rise until equilibrium is attained due to magnetic saturation in the machine. A breakthrough was achieved by evolving a specially designed 2 winding single phase SEIG with a self regulating capacitor topology [8] which has been recognised by Boldea as the most acceptable single phase SEIG. But it is observed that there is a heavy demand for small capacity generator in rural sector.…”
Section: Introductionmentioning
confidence: 99%
“…The induced emf and current in the stator winding will continue to rise until equilibrium is attained due to magnetic saturation in the machine. A breakthrough was achieved by evolving a specially designed 2 winding single phase SEIG with a self regulating capacitor topology [8] which has been recognised by Boldea as the most acceptable single phase SEIG. But it is observed that there is a heavy demand for small capacity generator in rural sector.…”
Section: Introductionmentioning
confidence: 99%